2018
DOI: 10.1515/npprj-2018-3018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nanocomposite polypyrrole/cellulose nanocrystals for conductive paper

Abstract: AbstractThe preparation of conductive polypyrrole (PPy) nanocomposite with cellulose nanocrystals (CNC) was carried out by situ polymerization method. The new water dispersible sample (PPy-CNC) was deposited as a thin film on the paper sheet substrate as a conductive paper. The images of field emission scanning electron microscopy (FESEM) clearly shw the morphological modulation and the uniformity of the PPy-CNC sample. The electrical properties of conductive paper were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…At the same time, the development prospects of fiber materials were discussed from the perspective of design frontiers in combination with the market. (2) We should first choose materials that save energy and have low carbon emissions. More consideration is given to the renewable resources created by nature to lay the foundation for the production of high-quality clothing and to achieve low carbon, environmentally, and friendly clothing design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the development prospects of fiber materials were discussed from the perspective of design frontiers in combination with the market. (2) We should first choose materials that save energy and have low carbon emissions. More consideration is given to the renewable resources created by nature to lay the foundation for the production of high-quality clothing and to achieve low carbon, environmentally, and friendly clothing design.…”
Section: Discussionmentioning
confidence: 99%
“…e experiment found that, with the decrease of pH value, mechanical properties such as tensile index and elongation at break decreased slightly. e results of elongation at break of 0.65pH sample showed different responses to pH value[2].Wang et al…”
mentioning
confidence: 99%
“…In the presence of the oxidant APS, Py is polymerized on the CNC surface to form a powerful PPy package, which is attributed to the effect of hydrogen bonding (see Figure 3 g). At the same time, PPy in PPy/CNCs composites also forms strong hydrogen bonds with the fiber substrate, which makes PPy/CNCs firmly attached to the fiber substrate [ 26 ]. The PPy/CNCs will readily be stacked layer upon layer to form composite materials conductive layer through order arrangement, disorder arrangement or orderly disorder coexistence (see Figure 3 h,i).…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose-water interaction, which gives -OH bending of absorbed water, is also observed at 1641 cm-1. The peak of C-Hasym bending was shown at 1019 cm -1 (C-O-C) and 903 cm -1 (C-Hdeform) modes of the β-glycosidic linkage between the anhydrous glucose rings (Al-Dulaimi & Wanrosli, 2017;Putri Amanda et al, 2020;Y. Sun et al, 2008).…”
Section: Ftir Spectroscopy Analysismentioning
confidence: 99%